TRAINING ON BIOGAS PRODUCTION FROM MANURE AND CONCRETE BRICK PRODUCTION TO IMPROVE THE ECONOMY OF CITIZEN IN DANAU SADAR VILLAGE, CENTRAL KALIMANTAN - Lilis Rosmainar; Karelius; Rasidah; Akhmad Damsyik; I Made Sadiana; Revianti Coenraad; Tia Monika (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
Danau Sadar Village is a village located in the sub-district of Dusun Selatan, 8 km from Buntok, the capital of South Barito Regency. This village has several potentials such as rubber plantation, livestock sector, tourism, and fisheries sector. Even though this potential is quite remarkable, the citizen welfare is still in low catagories due to the lack of skill in managing it. This condition happened because not all workers are engaged in the production process. Related to the condition of the community in Danau Sadar Village, an idea emerged to empower the community, by providing training to improve their skills. The objectives of community service in Danau Sadar Village are as follows: (1) assisting the people of Danau Sadar Village in developing economic independence; (2) improving entrepreneurial skills through the training provided. The community service program has been successful by carrying out two types of training activities to improve citizen welfare: training on biogas reactors from manure and brick making to obtain optimal products in terms of production costs and quality. The citizen in Danau Sadar Village welcomes this community service program. They hope that Palangka Raya University will carry out the community service program regularly in their village.